Impact of Hydrogeological Characteristics on the Development of Underground Space Resources in Valley Cities - Lizhong Zhang; Linde Liang; Jixiang Zhu; Tao Gan; Yamin Yang; Dun Wang (Geofluids)
The development of urban underground space is a crucial aspect of current urban development. However, various factors pose challenges during the development process. In particular, in the valley cities of western China, groundwater has a significant impact on the utilization of underground space. This study focuses on understanding the influence of hydrogeological characteristics on the development of underground space in Ledu District, Haidong. Firstly, the hydrogeological characteristics of the aquifer in the study area are analyzed to determine the recharge and discharge characteristics. The dynamic changes in the groundwater table over time are then examined. Subsequently, the hydrochemical characteristics of groundwater are investigated to expound on the influence mechanism of groundwater on the development of underground space resources in Ledu District. The study reveals that the hydrodynamic effect of groundwater in the study area is substantial and has a significant physical scouring effect on underground structures. The fluctuation of groundwater levels affects the stability of buildings by increasing groundwater buoyancy. Additionally, this fluctuation also leads to engineering and environmental problems such as differential settlement and land salinization. The chemical characteristics of groundwater primarily impact the stability of building foundations through the corrosive effects of groundwater composition. This research clarifies the influence mechanism of groundwater on the development of underground space in typical valley cities of western China. The findings have practical significance for the evaluation, planning, development, and utilization of urban underground space resources in Haidong.